TRAINING PROGRAMS NEEDED TO DEVELOP YOUNG ENTREPRENEURS FROM TRAINING INSTITUTIONS IN BANDUNG: A QUALITATIVE PERSPECTIVE - Syahrial Shaddiq; Eko Wanidison (UPMI Management, 2021)
Unemployment is a problem that is often faced by every country, especially developing countries like Indonesia. The high level of unemployment in a country can have a negative impact on the economy of a country. Entrepreneurship is the potential to build the economy for the better. Duta Transformasi Insani Bandung is one of the training institutions that can develop entrepreneurial potential. This study used a qualitative descriptive method. Researchers found that in organizing training for young entrepreneurs, one of the training evaluation techniques was adopted, namely IPOO. In terms of Input regarding the recruitment of training participants, the Process in this program aims to become more independent and free from dependence. The Output and Outcomes of the training participants are motivated to start a business and make it easier for them to manage themselves better.